The Importance of Arabic in Quran Study: Enhancing Understanding Through Native Language Learning - Khoerudin, Asep Rizal (UIN Sunan Gunung Djati Bandung, 2024)
The Arabic language is essential for Muslims to understand the Quran deeply, which is necessary for Quranic studies. Learning Arabic allows access to the Quran's original meanings, enabling accurate interpretation beyond translation limitations. It provides insights into the historical and cultural context of the Quran's revelation, enriching reflection on divine messages. Additionally, studying Arabic sharpens linguistic skills and enhances comprehension of sacred teachings and spiritual meanings. In conclusion, mastering Arabic is crucial for a comprehensive understanding of the Quran, deepening spiritual connections, and effectively applying its teachings. This study explores the critical relevance of the Arabic language in the thorough research of the Quran, emphasizing how native language learning can deepen one's understanding of the sacred text. The study adopts a qualitative approach, involving detailed analyses of linguistic and interpretative aspects of Quranic Arabic alongside interviews with Quranic scholars and students. It investigates the intrinsic connection between the Arabic language and the meanings conveyed in the Quran, highlighting the nuances and depth often lost in translation. The study further examines how learning Arabic as a native language facilitates a more profound engagement with the text, enabling learners to grasp its subtleties, rhetorical devices, and cultural contexts. Findings suggest that native language learning enhances comprehension and enriches the spiritual and intellectual experience of studying the Quran. The research underscores the importance of integrating native language pedagogy in Quranic studies to foster a deeper, more authentic connection with the text. This study contributes to religious education by advocating for a more linguistically immersive approach to Quranic research, promoting a holistic understanding of its teachings.